KONTRIBUSI KARATE DAN TAI CHI TERHADAP GERAK TARI GAGAH, ALUS DAN PUTRI GAYA SURAKARTA - Supriyanto, Mt. (Institut Seni Indoensia Surakarta, 2010)
This research conveys haw far the contribution of Karate and Tai Chi Chuan towards the movement ofÂ reï¬ne, dashing, and female dances is. Karate and Tai Chi are physical exercises given in Olah TubuhÂ (ï¬tness) course in semester llâ€™. One of the body treatments is the use of techniques or subjects in kinds ofsport such as Karate and Tai Chi. Kind of Karate namely self defense art comes from Japan while kind ofÂ Tai Chi namely self defense art comes from China. The diï¬‚erence between them is in case of charactenÂ Karate has hard, strict, and stnong character while Tai Chi has soft, slow, and streaming character. Bothhave training disciplinary that is useful for the development of traditional dance especially in supportingÂ the dance quality increase. As we can see that the physical aspects in body treatment are the same as thoseÂ in dance covering reï¬ne, dashing, and female dances. The aspects include power. endurance. balance.Â ï¬‚exibility, speed, liveliness, coordination, and accuracy. This research is descriptive qualitative namelyÂ the method which collecting data based an observation and interview. The data founded include data andÂ picture. The result of this research gives much contribution in increasing movement awareness andconcentration. dance deepening and enriching dance vocabularies.Key words: tai chi, karate, the movement of reï¬ne and dashing dances, dance of Surakarta style.